1998
DOI: 10.1183/09031936.98.12020408
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-altitude periodic breathing on sleep and arterial oxyhaemoglobin saturation

Abstract: This study aimed to investigate the effect of periodic breathing (PB) at high altitude on sleep structure and arterial oxygen saturation (Sa,O2). Five healthy subjects underwent polysomnographic studies at sea level, and during the first and the fourth week of sojourn at 5,050 m. Their breathing pattern, sleep architecture and Sa,O2 were analysed. PB was detected in the high-altitude studies during nonrapid eye movement (NREM) sleep and tended to increase from the first to the fourth week. Stages 3-4 were abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
48
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 17 publications
5
48
1
2
Order By: Relevance
“…Study medication was either oral slow release theophylline (26250 mg?day -1 ), oral acetazolamide (26250 mg?day -1 ) or a matched placebo tablet. Polysomnographic measurements were performed during two consecutive nights, and acute mountain sickness, pulse rate, oxyhaemoglobin saturation and arterial blood gases were assessed three times a day.Without active medication, the apnoea/hypopnoea index (AHI) was highly pathological ( Sleep-disordered breathing (SDB) of the Cheyne-Stokes type is commonly found during sleep at high altitude [1][2][3]. This typical breathing pattern with waxing and waning of the tidal volume is associated with profound desaturations and reduced overall oxygen saturation during sleep, but its association with an increased number of arousals is a matter of ongoing debate [4,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Study medication was either oral slow release theophylline (26250 mg?day -1 ), oral acetazolamide (26250 mg?day -1 ) or a matched placebo tablet. Polysomnographic measurements were performed during two consecutive nights, and acute mountain sickness, pulse rate, oxyhaemoglobin saturation and arterial blood gases were assessed three times a day.Without active medication, the apnoea/hypopnoea index (AHI) was highly pathological ( Sleep-disordered breathing (SDB) of the Cheyne-Stokes type is commonly found during sleep at high altitude [1][2][3]. This typical breathing pattern with waxing and waning of the tidal volume is associated with profound desaturations and reduced overall oxygen saturation during sleep, but its association with an increased number of arousals is a matter of ongoing debate [4,5].…”
mentioning
confidence: 99%
“…Sleep-disordered breathing (SDB) of the Cheyne-Stokes type is commonly found during sleep at high altitude [1][2][3]. This typical breathing pattern with waxing and waning of the tidal volume is associated with profound desaturations and reduced overall oxygen saturation during sleep, but its association with an increased number of arousals is a matter of ongoing debate [4,5].…”
mentioning
confidence: 99%
“…When respiratory events are cyclic and contain apneic episodes, this is known as periodic breathing (19). Periodic breathing has been observed during sleep in mountaineers, high-altitude residents, and sedentary sojourners from sea level during sleep at altitudes between 3,200 and 7,167 m (24,29,35). Periodic breathing has also been documented in awake individuals exposed to short-term hypoxia equivalent to 2,440 m (33).…”
mentioning
confidence: 99%
“…Sleep at altitude is often characterized by periodic breathing which is correlated with more arousals, although sleep is has been shown to be more disrupted at altitude regardless of the amount of periodic breathing. 110 These factors typically lead to sleep disruptions at altitude that reduce the quality of sleep for individuals during altitude residence that do not appear to diminish over the first few nights at altitude. 95,110 However, many individuals experience sleep disruptions in unfamiliar environments regardless of altitude.…”
Section: Altitude Exposure and Sleep Qualitymentioning
confidence: 99%
“…110 These factors typically lead to sleep disruptions at altitude that reduce the quality of sleep for individuals during altitude residence that do not appear to diminish over the first few nights at altitude. 95,110 However, many individuals experience sleep disruptions in unfamiliar environments regardless of altitude. The current study showed that the disruptions in sleep were not greater at altitude than they were from simply sleeping in a new environment, as there was no difference in sleep quality between the altitude conditions and control (normoxia).…”
Section: Altitude Exposure and Sleep Qualitymentioning
confidence: 99%